Hepatitis B surface antigen loss after discontinuing nucleos(t)ide analogue for treatment of chronic hepatitis B patients is persistent in White patients. Issue 2 (February 2019) - Suárez, Emilio; Buti, María; Rodríguez, Manuel; Prieto, Martín; Pascasio-Acevedo, Juan M.; Casanovas, Teresa; Crespo, Javier; Tapiador, Juan Arenas Ruiz; Gómez-Rodríguez, Rafael; Figueruela, Blanca; Diago, Moisés; Morillas, Rosa M.; et al.
Abstract : Objective: The objective of this study was to determine the long-term clinical outcome and persistence of hepatitis B surface antigen (HBsAg) loss after discontinuation of treatment. Background: The prognosis of patients with chronic hepatitis B (CHB) treated with nucleos(t)ide analogues (NAs) who discontinue treatment after loss of HBsAg remains largely unknown, particularly in White patients. Patients and methods: We analysed a cohort of patients with CHB who discontinued NA treatment after loss of HBsAg. A total of 69 patients with hepatitis-B-e antigen-positive or hepatitis-B-e antigen-negative CHB with undetectable HBsAg during NA treatment were included after discontinuation of treatment, and followed up for a median period of 37.8 months (interquartile range: 23.8–54.6 months). Results: At the end of follow-up, none of the patients showed spontaneous reappearance of HBsAg and only one patient had detectable hepatitis B virus DNA (22 IU/ml). Another patient negative for HBsAg and anti-HBs developed hepatitis B virus reactivation without elevated transaminases after treatment with corticosteroids and vincristine for dendritic cell neoplasm, 38 months after withdrawal of the antiviral treatment. Regarding clinical outcome, a patient with cirrhosis developed hepatocellular carcinoma, 6.6 years after discontinuing treatment. None of the patients had hepatic decompensation or underwent liver transplantation. Conclusion: HBsAg clearance after discontinuing NAs in patients with CHB is persistent and associated with good prognosis. The risk for developing hepatocellular carcinoma persists among patients with cirrhosis.